1979
DOI: 10.1080/10862967909547327
|View full text |Cite
|
Sign up to set email alerts
|

The Processing Strategies of average and below Average Readers Answering Factual and Inferential Questions on Three Equivalent Passages

Abstract: Abstract. This study examines the processing strategies of average and below average readers in response to factual and inferential questions. Thirty-six sixth and seventh grade students were given three equivalent passages of 1500 words to read. With each passage, Ss were given four factual and four inferential questions, placed as pre-questions, post-questions, or interspersed questions. The Ss, tested individually, answered the adjunct questions orally and were probed for explanations of their answers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Moreover, justifications of types 3 (where the answers were justified simply by pointing out a word or a sentence from the text that matched the words in the questions or the responses provided) and 4 (vague justifications) showed that children's ability to give a correct response is not necessarily linked to their ability to explain it. This was already suggested by Wilson's (1979) report of correct answers followed by ''incorrect reasons''. In the present study, however, it was possible to clarify such inadequate reasons.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, justifications of types 3 (where the answers were justified simply by pointing out a word or a sentence from the text that matched the words in the questions or the responses provided) and 4 (vague justifications) showed that children's ability to give a correct response is not necessarily linked to their ability to explain it. This was already suggested by Wilson's (1979) report of correct answers followed by ''incorrect reasons''. In the present study, however, it was possible to clarify such inadequate reasons.…”
Section: Discussionmentioning
confidence: 82%
“…The categories created here to account for the children's justifications of their responses go beyond the classification of ''correct'' or ''incorrect'' explanations as was done in Wilson's (1979) study, where older children (from 6th and 7th grades) were asked to show in the text how they had arrived at the answers they had given. An effort was made to generate a small number of categories sufficient to provide a clear picture of how young readers use the text and their own prior knowledge to justify their responses to comprehension questions.…”
Section: Justifications For Answersmentioning
confidence: 99%
“…When the comprehension task has consisted of post questions, good readers have also performed better than the poor readers (Berger & Perfetti, 1977;Oaken, Wiener, & Cromer, 1971;Schachter, 1980). In an effort to remove difficulty level of the text as a factor, some researchers have used passages below the grade placement level of the subjects (Schreiner & Shannon, 1980;Wilson, 1979). In these studies, good readers were still significantly better than poor readers in answering both factual and inferential questions.…”
mentioning
confidence: 99%
“…Reading researchers-such as Garner (1980), Golinkoff (1975), Sullivan (1978), and Wilson (1979)-have settled on a theory that poor readers can be taught to read by showing them how good readers approach text, i.e., a modeling approach. Good readers do what is referred to as "text monitoring" (Markman, 1977;Ringel & Springer, 1980), creating a schema of ideas, a thread of discourse, as they read.…”
Section: Remediating Sabrina's Reading Problemsmentioning
confidence: 99%